Visual status following contact lens related microbial keratitis - Ismail, Lili Asma; Gyanchand Rampal, Lekhraj Rampal; Omar, Nazri; Abdul Rahman, Hejar; Midi, Habshah; Ariffin, Azrin Esmady (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2016)
Introduction: A hospital based case control study was conducted in government hospitals on contact lens patients diagnosed with microbial keratitis. Methods: The objective of this study is to determine the visual outcomes of contact lens related microbial keratitis. The visual outcomes which comprised of visual acuity, keratometry readings, corneal topography findings and contrast sensitivity examinations was determined after three months from the first presentation at the hospitals. Results: The mean LogMAR visual acuity during presentation was 0.96 ± 0.73 or a Snellen equivalent 6/60 (n=76) and mean LogMAR visual acuity after three months was 0.10 ± 0.48 or a Snellen equivalent 6/7.5 (n=76) with a significant difference (t=11.22, df=78, p=0.001). Best fit curve for the cases had a regression coefficient, r=0.350 ± 0.063 (95% CI = 0.224, 0.447, df=78, p=0.001. The visual acuity in cases and controls was 0.10 ± 0.48 and -0.10 ± 0.14 respectively (t= -3.61, df=154 p=0.001) after three months which showed improvement. There was a reduction in the corneal uniformity index and corneal asphericity in the cases. The Corneal Uniformity Index (CU index) in cases was 63.03 ± 26.38 (n=76) and in controls, 80.13 ± 11.30 (n=77), (t= -5.22, df=151, p=0.001). There was also a reduction in the contrast sensitivity function at all spatial frequencies in the cases which was significantly different. Conclusion: Microbial keratitis reduced the vision, corneal uniformity index, asphericity and contrast sensitivity after three months in eyes of patients diagnosed with the condition.